Indicadores de balanço energético negativo em vacas leiteiras no início de lactação - Capelesso, Alsiane Simone (2015)
Early lactation in dairy cows involves metabolic changes, being mobilization of corporal reserves very common. So the objective of this work is to study indexes of negative energetic balance in dairy cows on early lactation, in two different energy levels. For this, 20 cows were distributed in a randomized complete block design, resulting in 2 treatments: T1 one milking per day for 8 weeks on the beginning of lactation and T2 two milkings for the same period of time. In animals, it was measured live weight, body condition scoring, skinfold thickness, being also collected blood samples for non-esterified fatty acids, urea, glucose, acetoacetate and Dβ-Hydroxybutirate analyses. It was also realized urea dilution measurements. As a result dry matter intake wasn´t different between treatments, milk production and milk solids in kg were lower for T1. For differences analyses T1 resulted in a better energy balance for the treatment period (P = 0.0002), obtaining the opposite result for residual period (P = 0.0423). Talking about corporal characteristics, corporal protein was statistically different between the treatments only for residual period, being higher for T1 (P = 0.0463), meanwhile in blood measures, non-esterified fatty acids (P = 0.0352) and Dβ-Hydroxybutirate (P = 0.0004), were lower for T1, for treatment period. Dβ-Hydroxybutirate didn´t show relation with energy balance, so more studies must be done.